The Performance of Hedge Fund Styles in the Crisis and Post-Crisis Periods - Miettunen, Matias (My University, 2016)
Hedge funds are considered alternative investment vehicles for traditional asset classes and to exhibit a low correlation with the stock market. The purpose of this study is to investigate the performance of various hedge fund strategies during both the crisis and post-crisis periods and to discover whether returns of those strategies are significantly affected by positive and negative returns of the S&P 500 index. The research period is divided into two contrasting periods based on previous literature. The crisis period begins in August 2007 and ends in March 2009. Respectively, the time frame for the post-crisis period is set to start in April 2009 and end in December 2015. The research data consists of monthly index returns of the different hedge fund strategies and it is obtained from the Hedge Fund Research database. The examined investment styles are categorized into six primary strategy groups and their 20 sub- categories. The performance of the hedge fund styles is measured with absolute returns and using three risk-adjusted models, which are Sharpe ratio, Sortino ratio and Jensen’s alpha. The impact of S&P 500 returns on hedge fund returns is tested with the Ordinary Least Squares regression, which captures the mean effect of the explanatory variables on the explained variable. The quantile regression estimates the similar impact at various quantiles, simultaneosly serving as a robustness check for the OLS results. On a risk-adjusted basis, none of the examined hedge fund indices produced positive returns during the recent financial crisis. The performance was substantially better in the post-crisis period, although there were no signs of performance persistence among the best-performing styles. Moreover, the majority of hedge fund index returns were significantly affected by market index returns. This impact was stronger post-crisis and negative returns had a more significant impact compared to positive returns. The results indicate that hedge funds are not able to eliminate systematic risk during financial distress. Furthermore, only a few hedge fund styles provide diversification benefits for investors. Therefore, when investing in hedge funds, it is beneficial to perform a comprehensive analysis of investment strategies and managers’ skills.
Keywords: Hedge fund; Investment strategy; Performance; Correlation; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|